Characterizing tobacco and marijuana use among youth combustible tobacco users experiencing homelessness - considering product type, brand, flavor, frequency, and higher-risk use patterns and predictors - Allison M. Glasser; Alice Hinton; Amy Wermert; Joseph Macisco; Julianna M. Nemeth (BMC, 2022)
Abstract Background Cigarette smoking is three times more prevalent among youth experiencing homelessness compared with the general population. Co-use of tobacco and marijuana is also common. The aim of this study is to characterize tobacco and marijuana use among youth experiencing homelessness who use combustible tobacco in a Midwestern city to inform smoking cessation intervention. Methods This study included 96 youth (ages 14-24 years; 52% male, 39% female, 5% transgender/non-binary) attending a homeless drop-in center who had used at least one combustible tobacco product in the past week. We assessed past-month use of tobacco products and marijuana, other product use characteristics (e.g., frequency, brand and flavor), and psychosocial predictors of more frequent (i.e., daily) use of combustible tobacco and marijuana. Results Most youth experiencing homelessness with past-week combustible tobacco use had used cigarettes (n = 85, 88.5%), cigars (n = 89, 92.7%), and marijuana (n = 82, 85.4%) in the past month. One-third (n = 34) used electronic vapor products (EVPs), 19.8% (n = 19) smoked hookah, and 11.5% (n = 11) used smokeless tobacco (ST). Most marijuana users co-administered with tobacco (n = 67, 69.8%). Daily combustible tobacco smoking was associated with having a child and smoking out of boredom/habit. Daily marijuana use was associated with using substances to cope with one's housing situation. Newport (n = 66, 72.5%) and Black & Mild (n = 48, 51.1%) were the most popular brands of cigarettes and cigars among ever users. Most non-combustible tobacco ever users reported not having a usual brand (EVPs: n = 51, 73.9%; ST: n = 16, 57.1%). Cigar smokers reported the most varied selection of flavors. Conclusions Young combustible tobacco users experiencing homelessness engage in high-risk use patterns, including poly-tobacco use, co-use of tobacco with marijuana, and frequent combustible product use. Interventions that consider the full context of tobacco and marijuana use are needed to support smoking cessation in this population.